Are myelodysplastic syndromes underdiagnosed in Poland? A report by the Polish Adult Leukaemia Group. (1st November 2016) - Drozd‐Sokołowska, Joanna E.; Mądry, Krzysztof; Waszczuk‐Gajda, Anna; Żółtak, Tomasz; Sikorska, Anna; Mital, Andrzej; Wajs, Jarosław; Semeńczuk, Grażyna; Szmigielska‐Kapłon, Anna; Szczepańska, Magdalena; Wasilewska, Ewa; Szwedyk, Paweł; et al.
Abstract: Objectives: The epidemiology of myelodysplastic syndromes (MDS) differs among countries. Here, we present the first epidemiological indices determined for Poland. Methods: Twenty‐one haematological centres participated in the study. Patients diagnosed with MDS and acute myeloid leukaemia (AML) with 20–29% blasts were enrolled. Data collection was conducted for strictly predefined period. Results: The overall crude incidence rate for all MDS subtypes was 1.95 (95% CI, 1.81–2.09) per 100 000 person‐years: 2.46 (95% CI, 2.24–2.69) for males and 1.47 (95% CI, 1.31–1.65) for females; after excluding AML cases, the indices were as follows: 2.35 (95% CI, 2.08–2.66) for males and 1.27 (95% CI, 1.08–1.5) for females. Prevalence rate was 6.2 per 100 000 persons (95% CI, 5.96–6.45), that is 6.86 (95% CI, 6.49–7.24) for males and 5.58 (95% CI, 5.26–5.92) for females. Both incidence and prevalence increased with increasing age. The most frequently diagnosed MDS subtype was refractory cytopenia with multilineage dysplasia (RCMD), responsible for 30.3% of all newly diagnosed MDSs. Conclusions: RCMD is the most frequent MDS subtype in Poland. Incidence and prevalence indices are lower than those reported for other populations, which probably results from inadequate diagnosis of potential cases of this disease.